Understanding Patterns of Social Support and Their Relationship to an ART Adherence Intervention Among Adults in Rural Southwestern Uganda - Atukunda, Esther Cathyln; Musiimenta, Angella; Musinguzi, Nicholas (open access at Springerlink.com, 2006)
Abstract SMS is a widely used technology globally and may also improve ART adherence, yet SMS notifications to social supporters following real-time detection of missed doses showed no clear benefit in a recent pilot trial. We examine the demographic and social-cultural dynamics that may explain this finding. In the trial, 63 HIV-positive individuals initiating ART received a real-time adherence monitor and were randomized to two types of SMS reminder interventions versus a control (no SMS). SMS notifications were also sent to 45 patient-identified social supporters for sustained adherence lapses. Like participants, social supporters were interviewed at enrollment, following their matched participant’s adherence lapse and at exit. Social supporters with regular income (RR = 0.27, P = 0.001) were significantly associated with fewer adherence lapses. Instrumental support was associated with fewer adherence lapses only among social supporters who were food secure (RR = 0.58, P = 0.003). Qualitative interview data revealed diverse and complex economic and relationship dynamics, affecting social support. Resource availability in emotionally positive relationships seemingly facilitated helpful support, while limited resources prevented active provision of support for many. Effective social support appeared subject to social supporters’ food security, economic stability and a well-functioning social network dependent on trust and supportive disclosure.
Keywords: Social support; Adherence; Relation dynamics; ART; Uganda